Dysphoric Milk Ejection Reflex: The Psychoneurobiology of the Breastfeeding Experience - Deif, Reem; Burch, Emily Michelle; Azar, Jihan; Yonis, Nouran; Abou Gabal, Macy; El Kramani, Nabila; DakhlAllah, Duaa (Frontiers in Global Women's Health, 2021)
Breastfeeding, given its biochemical and physiological basis, is known for its many benefits for both the lactating mother and the infant. Among the many challenges new breastfeeding mothers experience is the feeling of aversion in response to their newborn's suckling which has been termed dysphoric milk-ejection reflex (D-MER). Characterized by intense feelings of dysphoria which may eventually interfere with the mother's ability to breastfeed regularly, evidence suggests both the neurobiological and psychological basis of D-MER in an attempt to explain its complexity. Biologically, breastfeeding is expressed by the intracerebral release of oxytocin, an increased expression of oxytocin receptors in specific brain regions, increased mesocorticolimbic reward region activation, the secretion of prolactin and possibly the inhibition of dopamine. Hence, different theories explain D-MER in terms of disrupted neurotransmitter and hormonal activity. Breastfeeding has also proven to influence mood and stress reactivity in nursing mothers with a potential link with postpartum depression. Psychological theories attempt to explain D-MER from a sociopsychosexual lense shedding light on the significance of mother-infant attachment, the sexualization of the female body and the motherhood experience as a developmental stage in a woman's lifespan. The aim of this review is to provide a literature update of D-MER incorporating both neurobiological and psychological theories calling for raising awareness about the complexity of breastfeeding and for the need for mother-centered interventions for the management of D-MER and other postpartum-specific conditions.